SOSIALISASI POTENSI INDUSTRI KREATIF DI PASAR EROPA UNTUK PARA UMKM KAMPUNG BATIK LAWEYAN SOLO - GPH. Dipokusumo & Halifa Haqqi (Adi Widya : Jurnal Pengabdian Masyarakat, 2018)
Cultural and Creative Industries (CCIs) shows a significant increase, both globally and locally. The market for creative industries in Europe is also wide open. For Indonesia, the creative industry sector is also a leading sector. Unfortunately, many creative industry players do not understand the potential of this. Therefore, it is important to provide information about creative industry’s export potential to Europe. The method used in this program is through socialization and disccusion. The program has been held with participants in creative industries, located in Kampung Batik Laweyan Surakarta. The socialization program was held on Sunday, October 28, 2018 located in Batik Laweyan Village. Through this program, it can be useful for: (1) creative industry players, to get an overview of the potential of the creative industry in the European market; (2) for the region, can develop regional potential, regional promotion, and regional economic development; (3) for universities, as a fulfillment of the Tri Dharma elements of Higher Education. The output of this program are that the participants can understand and encouraged to export their creative industries product to the European market.Keywords: creative industry, Europe market, export, Kampung Batik Laweyan